RESEARCH OF FEATURES OF DECREASE IN RISK AND UNCERTAINTY OF INNOVATIVE ACTIVITY OF THE INDUSTRIAL ENTERPRISE - I. Galetov; A. Zhelezin; M. Avanesyan (Вестник университета)
The mechanism of decrease in uncertainty and risk of innovative activity of the industrial enterprise is offered. On the basis of the established dependences of change of risk level on stages of innovative process effective management of adaptation of innovative processes can be carried out by a certain type of risk, and in that period when this type of risk poses the greatest threat to all innovative process.